Macromolecular Drug Targets in Cancer Treatment and Thiosemicarbazides as Anticancer Agents - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (BENTHAM SCIENCE PUBL LTD, 2016)
Cancer is known as abnormal cell division and consisting of a group of diseases on various organ tissues. Many therapies are available in cancer treatment such as chemotherapy, radiotherapy etc. Without damaging normal tissue, there is a huge need for specified anticancer drugs which have effect only on abnormal cancer cells. Therefore, advances in anticancer drug discovery in treating cancer in the recent years, directed towards to the macromolecular targets. Heterocyclic molecules, such as fluconazole, acetazolamide, etc., have a significant role in health care and pharmaceutical drug design. Thiosemicarbazides (NH2-NH-CSNH2) are the simplest hydrazine derivatives of thiocarbamic acid and are not only transition compounds, but they are also very effective organic compounds. Thiosemicarbazides possess an amide and amine protons, carbonyl and thione carbons. These structures have attracted the attention of the researchers in the development of novel compounds with anticonvulsant, antiviral, anti-inflammatory, antibacterial, antimycobacterial, antifungal, antioxidant and anticancer activities. Recently, a number of thiosemicarbazides are available commercially as anticancer drugs for novel anticancer drug discovery. Antineoplastic or anticancer drugs prevent or inhibit the maturation and proliferation of neoplasms. These observations have been guiding the researchers for the development of new thiosemicarbazides that possess anticancer activity.
Keywords: Thiosemicarbazide; hydrazinocarbothioamide; anticancer; apoptosis; caspase-3; isothiocyanate; NAD-DEPENDENT OXIDATIONS; BIOLOGICAL EVALUATION; SUBSTITUTED THIOSEMICARBAZIDES; ANTICONVULSANT ACTIVITY; ANTIMICROBIAL ACTIVITY; ANTITUMOR-ACTIVITY; 1,4-DISUBSTITUTED THIOSEMICARBAZIDE; INHIBITORY-ACTIVITY; POTENT INHIBITORS; MOLECULAR DOCKING